Computational Insights into Excited State Intramolecular Double Proton Transfer Behavior Associated with Atomic Electronegativity for Bis(2′-benzothiazolyl)hydroquinone - Zhao, Jinfeng; Liu, Chang (Molecules (Basel, Switzerland), 2023)
Inspired by the distinguished regulated photochemical and photophysical properties of 2-(2′-hydroxyphenyl)benzazole derivatives, in this work, the novel bis(2′-benzothiazolyl)hydroquinone (BBTHQ) fluorophore is explored, looking at its photo-induced behaviors associated with different substituted atomic electronegativities, i.e., BBTHQ-SO, BBTHQ-SS and BBTHQ-Se compounds. From the structural changes, infrared (IR) vibrational variations and simulated core-valence bifurcation (CVB) indexes for the dual hydrogen bonds for the three BBTHQ derivatives, we see that low atomic electronegativity could be conducive to enhancing hydrogen bonding effects in the S1 state. Particularly, the O4-H5⋯N6 of BBTHQ-SO and the O1-H2⋯N3 of BBTHQ-SSe could be strengthened to be more intensive in the S1 state, respectively. Looking into the charge recombination induced by photoexcitation, we confirm a favorable ESDPT trend deriving from the charge reorganization of the dual hydrogen bonding regions. By constructing the potential energy surfaces (PESs) along with the ESDPT paths for the BBTHQ-SO, BBTHQ-SS and BBTHQ-Se compounds, we not only unveil stepwise ESDPT behaviors, but also present an atomic electronegativity-regulated ESDPT mechanism.